Group Counseling in the Perspective of Islamic Counseling: Halaqah Mentoring Vs Group Guidance - Fitriana Fitriana (Universitas Muhammadiyah Enrekang, 2024)
This research explores the comparison between two counseling approaches, namely halaqah mentoring in Islam and conventional group counseling, to understand how they can complement each other in achieving the holistic well-being of individuals. Halaqah mentoring, a traditional method in Islamic education, emphasizes spiritual and moral development, while conventional group counseling is more oriented towards psychological problem-solving and individual skill development. This comparison highlights the differences in goals, techniques, and cultural context between the two approaches. Despite the fundamental differences, research shows that the two can be integrated to provide more holistic support for individuals, especially in contexts that require a holistic approach. The research method used was a literature review with a qualitative approach, using content analysis techniques to synthesize findings from various sources. The results show that Islamic counseling with halaqah mentoring presents an approach that integrates Islamic values into the counseling process, while conventional group counseling offers a more directed and structured approach. By understanding the strengths and weaknesses of each approach, counselors can optimize their use to best support individuals in diverse contexts.